Analisis Implementasi Pola Kemitraan Kehutanan dalam Skema Perhutanan Sosial (PS) di Kalimantan Tengah: Studi Kasus Lanskap Rungan - Mariaty, Mariaty; Purba, Daud; Rosawanti, Pienyani (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Forest partnership is one of the five schemes within the Social Forestry policy framework, aiming to improve the welfare of communities living in and around forest areas. Despite having a legal foundation through Ministerial Regulation of Environment and Forestry No. 09 of 2021 and Government Regulation No. 23 of 2021, its implementation in Central Kalimantan remains limited. This study analyzes the potential, challenges, and opportunities of forest partnership using a case study approach in the Rungan Landscape, which spans approximately 517,313 hectares and includes various forestry permits. The analysis reveals that although there is a potential for up to ±60,000 hectares of partnership area using a plantation plasma model, not a single Forest Partnership Agreement (NKK) has been realized. The main obstacles include differences in perception, bureaucratic procedures, and limited facilitation. The study recommends the development of regional policies, increased outreach efforts, and the involvement of universities as facilitators in the formulation and implementation of partnerships.